Similarity Between Adults and Regenerants of the Tree Component in Araucaria Forest Similaridade entre Adultos e Regenerantes do Componente Arbóreo em Floresta com Araucária - de Aguiar M.D. (2017)
© 2017. All Rights Reserved.This study aimed to inventory the tree regenerating component in a forest in Southern Plateau of Santa Catarina and compare it to the adult component of the same area. A total of 25 plots were allocated, where the regenerating and adults trees were identified and quantified. The Total Natural Regeneration Index (TNR) of each species was calculated. We used the analysis of similarities and the Jaccard index to verify the similarity between the components. A total of 503 regenerants belonging to 58 species and 29 families were sampled. Myrtaceae was the richest family (13). Leandra regnelli (Triana) Cogn., Myrcia splendens (Sw.) DC. and Miconia cinerascens Miq. showed the highest values of TNR. There was elevated dissimilarity between the regenerative and adult component, with 37.5% of the species adult component absent on natural regeneration. In conclusion, there is a low regenerative capacity of most species which may be associated with the presence of cattle in the area.